2021
DOI: 10.1108/ilt-03-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Tribological study of TiO2 nanoparticles modified with stearic acid as additives in lithium grease

Abstract: Purpose The purpose of this paper is to improve the properties of metal nanoparticles which are easy to agglomerate and hard to disperse evenly, thus limiting the application of metal nanoparticles in grease. A novel technology was proposed for modifying metal oxide to improve the dispersibility of nanoparticles. Design/methodology/approach SA-TiO2 nanoparticles were synthesized using an in-situ esterification method followed by surface modification with stearic acid. The microstructure of the nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The band gap of unmodified ZnO NRs, ZnO(SA1), ZnO(SA2), and ZnO(SA3) are 3.31 eV, 3.29 eV, 3.27 eV, and 3.26 eV respectively. There is no appreciable change in band gap of ZnO NRs after modification with stearic acid [71] …”
Section: Resultsmentioning
confidence: 96%
“…The band gap of unmodified ZnO NRs, ZnO(SA1), ZnO(SA2), and ZnO(SA3) are 3.31 eV, 3.29 eV, 3.27 eV, and 3.26 eV respectively. There is no appreciable change in band gap of ZnO NRs after modification with stearic acid [71] …”
Section: Resultsmentioning
confidence: 96%
“…Because the testing time of the UMT experiments is limited, it can only explain the high-temperature lubrication performance in a short time but long-term operation. Considering that the main failure modes of greases in high-temperature environments are oxidation deterioration and high-temperature evaporation, we have done several sets of thermal gravimetric analysis (TGA) experiments and differential scanning calorimetry (DSC) experiments of greases to judge the long-term stability of the grease in high-temperature environment (Xu et al , 2017; Zhang et al , 2021; Qi et al , 2021). Therefore, TGA and DSC experiments were done for the grease to explain its long-term lubrication performance in high temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Kumar et al [56] reported the potential of nanoparticles (NPs) of Talc to improve the tribo-performance of Li-based grease in antiwear and extreme-pressure. What's more, Rylski and Siczek [57] and Zhang et al [58] found that the improvement of the dispersibility of nanoparticles can effectively improve the tribology performance of lithium grease with preventing the agglomeration of nanoparticles. These are consistent with the study of Wang et al [59] about the influence of the variation of morphology on the tribological performance of layered double hydroxide (LDH).…”
Section: Grease Lubricationmentioning
confidence: 99%
“…Kajita et al [877] proposed an Fig. 58 Molecular dynamics and machine learning methods in EHL simulation [873,877]. Reproduced with permission from Ref.…”
Section: Lubricant Theory and Designmentioning
confidence: 99%